Change and the nation-state in the European Union - Haastrup, Adetoun A A (Department of Political Studies, 2016)
The advent of the European Union has necessitated an adaptation on the part of governments, especially in those areas where the Community's laws supersede the national laws. The process whereby the Union affects the state has been characterised as ' Europeanisation.' This paper examines the adaptation in certain policy areas, not of policy itself, but at changes in the decision-making mechanisms that accompany membership in Union. It focuses on change in foreign policy mechanisms in Britain and Sweden, both unique case studies because of their histories. I argue that changes in foreign policy mechanisms reflect a change in the construct of the state itself given the delicacy of this particular policy area. Because foreign policy making remains within the ambit of respective member states, with the CFSP, the second pillar of the Maastricht treaty, encouraging, at best coordination by states, without imposing supranationality, foreign policy coordination in the European Union is mostly an intergovernmental affair. The changes in decision-making mechanisms however, has jeopardised the accepted notion of sovereignty in EU states as Sweden battles to retain her neutrality identity and Britain struggles to keep its Atlantic alliance intact while being part of Europe. Moreover, although the present changes have not removed foreign policy within the Union from intergovernmental level, that position too is fast changing. It is too early to say that the CFSP or the CESDP will supersede national foreign policy, and possibly, for a long time it would not; however, the new mechanisms in place allow for change in this aspect of the Union. In essence, as national foreign policy mechanisms evolve to accommodate membership, the CFSP too is adapting to the influence of the states and in the final analysis has the most potential to shape the future of the Union.